Spectromicroscopic measurement of surface and bulk band structure interplay in a disordered topological insulator - Kotta, Erica; Lin, Miao; Xu, Yishuai; Breitweiser, S Alexander; Jozwiak, Chris; Bostwick, Aaron; Rotenberg, Eli; Zhang, Wenhan; Wu, Weida; Suzuki, Takehito; Checkelsky, Joseph; Wray, L Andrew (arXiv.org, 2019)
Topological insulators are bulk semiconductors that manifest in-gap massless Dirac surface states due to the topological bulk-boundary correspondence principle [1-3]. These surface states have been a subject of tremendous ongoing interest, due both to their intrinsic properties and to higher order emergence phenomena that can be achieved by manipulating the interface environment [4-11]. Here, angle resolved photoemission (ARPES) spectromicroscopy and supplementary scanning tunneling microscopy (STM) are performed on the model topological insulator Bi2Se3 to investigate the interplay of crystallographic inhomogeneity with the topologically ordered bulk and surface band structure. Quantitative analysis methods are developed to obtain key spectroscopic information in spite of a limited dwell time on each measured point. Band energies are found to vary on the scale of 50 meV across the sample surface, enabling single-sample measurements that are analogous to a multi-sample doping series (termed a "binning series"). Focusing separately on the surface and bulk electrons reveals a nontrivial hybridization-like interplay between fluctuations in the surface and bulk state energetics.